Advances in Organoid Research and Developmental Engineering - Hauser, Peter V. (Bioengineering (Basel), 2024)
Over the last decade, organoid research has emerged as a transformative field in biomedical science, offering unparalleled opportunities in disease modeling, pharmacological testing, and tissue engineering [...]